ENSURING A GIVEN RATIO OF QUALITY INDICATORS OF AN ELECTRICAL SYSTEM WITH INCOMPLETE MEASUREMENT OF THE STATE VECTOR - Kazurova, A. E.; Ivochka, N. V. (Radio Electronics, Computer Science, Control, 2024)
The flexible electromechanical system control, the specificity of which is the presence of elasticity and significant nonlinear friction on both control object and motor, is considered. Motor armature current, motor rotor speed and control object rotation angle and speed are measured. For this system the optimal in quick-action robust combined regulator with the observer of uncertainty and its compensation is synthesized. Computer simulation confirms the dynamic characteristics of the synthesized control system.